Pendampingan Usaha UMKM Deppa Tori’ : Optimalisasi Produksi dan Keuangan UMKM Deppa Tori’ sebagai Ikon Kuliner untuk Mendukung Pariwisata Lokal Toraja - Wilma Dian Ardiyanti; Marniati Marniati; Ellyn Patadungan; Winta Panimba; Randy Tangdialla (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
This community service program aims to assist Deppa Tori’ business actors in optimizing production and financial management in order to improve the quality, capacity, and sustainability of their business. The methods used in this program include training, direct assistance, and implementation of more efficient production strategies and more systematic financial records. In addition, this program also prioritizes branding and marketing aspects that are in line with local tourism potential, so that Deppa Tori’ can be better known as a typical souvenir that supports the tourism industry in the Toraja area. The expected results of this activity are increased production efficiency, better product quality standards, and a more organized financial system for Deppa Tori’ business actors. Thus, MSMEs can develop more professionally and contribute to strengthening the local creative economy and tourism sectors.